German foreign policy in transition: Volatile conditions, new momentum - Günther Maihold; Stefan Mair; Melanie Müller; Judith Vorrath; Christian Wagner (Stiftung Wissenschaft und Politik (SWP), 2021)
In the coming legislative period, the Federal Government and the Bundestag will need to redefine the scope of Germany's responsibility in world politics. The potential for action of German foreign policy cannot be properly assessed without taking into consideration the new international constellations and the required changes. Shifts in international power, the loss of influence of Western positions, growing authoritarianism, the weakening of multilateral institutions, urgent global problems such as climate change - all of these challenges call for a realignment of German foreign policy. In doing so, it is important to adequately assess the limits of its capabilities but also the existing room for manoeuvre. This should guide its goals and priorities. German foreign policy is faced with increasingly intense competition for international influence and the authority to interpret norms and values. This competition takes different forms in the individual fields of foreign affairs. For this reason, Germany's presence in international politics can only be influential if the ministries involved pool their efforts and resources. More room needs to be made available for forward-looking and medium-term approaches in foreign policy decision-making. In this way, it may be possible to overcome the tendency towards ad hoc decisions and to avoid predominantly reactive patterns of behaviour. Germany's foreign relations must be guided by reliable partnerships and new forms of responsibility-sharing in various policy areas. How conflicting objectives are to be negotiated can only be determined through open and transparent dialogue.
Keywords: 320